Cause, autonomy of the will and principle of individuation - Marcos Rodríguez Puentes (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales, 2023)
The concept of cause of contracts has been impro-perly addressed since Domat, causing a state of unintelligibility and legal doctrines that deem the cause irrelevant, excluding it from legal thinking, or excessively important, justifying an excessive intervention of the market. This paper aims to in-corporate to this legal discussion some psychologi-cal elements to guide the understanding of this con-cept, its relation with the autonomy of the will and, as a consequence, the adequate kind of governmen-tal intervention. Based on Joaquín Dualde’s ideas, I affirm that consent is the cause of contracts, and that the Law should look at the causes of such cau-se, that is to say, those elements and events which when manifested, configure the contract. I analyze the irrational elements of this configuration and, finally, based upon the Humanistic Psychology perspective and the individuation principle propo-sed by Carl Jung, I consider the possibility of effectively strengthening the effective freedom of people.